Quantification of factors influencing the road network damage using relative importance index method - Nur Azah, Ibrahim (2017)
This paper describes the survey for significant causes to road damage in Tanah Merah, Kelantan. Damage to road structure influence the optimal function and serviceability of the road line. Other than that, road damage expose the users with traffic accidents and contribute to country losses especially in road sector. This research enhance the public drivers’ knowledge about the most contributing factors to road damage and effective ways to keep the quality of the road. Then, a questionnaire was prepared based on literature review study, interview session with professional person that involved in the construction field and directed to 200 respondents involving the public drivers (licensed user) above eighteen (18) years old. The survey was involving to give a scale (rank) from 1 (strongly disagree), 2 (disagree), 3 (do not know), 4 (agree), and 5 (strongly agree) to the expected factors. From the data analysis using relative importance index (RII) method, review that group factors of vehicles overloading ranked the first RII with 0.883 which indicate the most influencing factors to road pavements failure. The second group of factors is traffic volume with 0.870 and followed by bad drainage system with 0.857. The government must take a serious action especially the heavy vehicles problems which can inhibits the road damage becomes worse, reschedule the maintenance work wisely and systematic.